2002
DOI: 10.1038/416406a
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-biased quantum tunnelling in a supramolecular dimer of single-molecule magnets

Abstract: Various present and future specialized applications of magnets require monodisperse, small magnetic particles, and the discovery of molecules that can function as nanoscale magnets was an important development in this regard. These molecules act as single-domain magnetic particles that, below their blocking temperature, exhibit magnetization hysteresis, a classical property of macroscopic magnets. Such 'single-molecule magnets' (SMMs) straddle the interface between classical and quantum mechanical behaviour be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
695
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 968 publications
(724 citation statements)
references
References 28 publications
27
695
0
2
Order By: Relevance
“…The calculated crossover temperature for the dimer is T c = 0.40 K in close agreement with experimental measurements [40]. Due to the weak exchange interaction every spin flips almost independently.…”
Section: Applications Molecular Magnetssupporting
confidence: 73%
See 2 more Smart Citations
“…The calculated crossover temperature for the dimer is T c = 0.40 K in close agreement with experimental measurements [40]. Due to the weak exchange interaction every spin flips almost independently.…”
Section: Applications Molecular Magnetssupporting
confidence: 73%
“…where bothĤ 1 andĤ 2 have the same form as (17) with the parameters taken from [39] and J = 0.12 K is isotropic superexchange [40]. The transverse term is chosen to include both 4th-and 2nd-order anisotropies: C(Ŝ 2 + +Ŝ 2 − ) and E(Ŝ 4 + +Ŝ 4 − ), with C = 0.032 K and E = −7.5 × 10 −5 K, in order to match the experimental results of the rate above T c .…”
Section: Applications Molecular Magnetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 3 shows very different physics from the exchange bias type of compounds, originally described by Wernsdorfer et al 33 , and also seen in {Dy 2 } complexes 16 , where a remnant magnetization is present in the open hysteresis loops; a feature not observed here because of rapid zero-field relaxation. The hypothetical compound where the tilt angle is 0°may possibly show the characteristic QTM steps at the crossing points in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 64%
“…7,8 In addition, MNMs exhibit a wide range of intriguing quantum phenomena, such as quantum tunneling of the magnetization, [9][10][11] decoherence, 12,13 or quantum entanglement between distinct cores. [14][15][16][17] MNMs also present great advantages from the standpoint of theoretical modeling. Indeed, it has been demonstrated that the effective spin Hamiltonian is a powerful model to describe magnetic properties of these clusters.…”
Section: Introductionmentioning
confidence: 99%